PENGEMBANGAN BAHAN BACAAN RAMAH ANAK UNTUK PENCEGAHAN KECANDUAN GAWAI - Putri, Ellyana Ilsan Eka; Oktaviana, Mimbar; Savira, Siti Ina; Satiningsih, Satiningsih; Moesarofah, Moesarofah (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The use of gadget besides resulted in positive impacts with this renewal of the rapid information and knowledge, unwittingly also had a negative impact, one of these is the dependence.The negative impact of the use of other gawai is uneasy if not gadget holds or operates, incapacitates the socialization of children, cognitive and ability.This will be more terrible if the role without of supervision the neighborhood or parents, so that the child does not have control over the use of gadget. This study attempts to develop reading materials friendly children to overcome addiction gadget in young junior high school. This study using ADDIE model was with developmental step of the 5, analisys, design, development, implementation, evaluation. Output of this research is give aspiration of reading materials to overcome gadget addiction that emerged in the community and the publication of articles.